Utilization of BaAl1.4Si0.6O3.4N0.6:Eu2+ Green-emitting Phosphor to Improve Luminous Intensity and Color Adequacy of White Light-emitting Diodes - Nguyen Le Thai; Thuc Minh Bui; Anh Tuan Le; Dieu An Nguyen Thi (International Journal of Technology, 2023)
BaAl1.4Si0.6O3.4N0.6:Eu2+ exhibiting broad excitation and emission bands with intense green emission centred at 510 nm is applied to produce high-performance white-light-emitting diodes (WLEDs). The preparation of the green phosphor utilizes NaNO3 molten salt to attain the purity phase and enhanced luminescence strength boosting the crystalline growth. The influences of BaAl1.4Si0.6O3.4N0.6:Eu2+ on the lighting intensity and color adequacy are investigated at three correlated color temperatures (CCTs) of 3000 K, 4000 K and 5000 K. The lighting output of the WLEDs with high CCTs (4000 – 5000 K) is deemed as enhanced with increasing green-phosphor concentration. The lower CCT shows greater lumen output when using a lower concentration of BaAl1.4Si0.6O3.4N0.6:Eu2+. This tendency also takes place in the case of color uniformity. Conversely, the high concentration of the phosphor is not favourable to the color rendition property of the WLED because of the excessive green-light proportion. It is recommended to keep the concentration of BaAl1.4Si0.6O3.4N0.6:Eu2+ staying below 10 wt% for better color fidelity.